2011
DOI: 10.4208/cicp.311009.091110s
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Collision Simulation by a Multi-Speed Lattice Boltzmann Method

Abstract: Abstract. Realization of the Shan-Chen multiphase flow lattice Boltzmann model is considered in the framework of the higher-order Galilean invariant lattices. The present multiphase lattice Boltzmann model is used in two-dimensional simulation of droplet collisions at high Weber numbers. Results are found to be in a good agreement with experimental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In 1999, He et al [45] proposed an incompressible LB model for simulating multiphase flows, in which they used an index function to track the interface between different phases. Two distribution functions were employed in the model, the index distribution function f  and the pressure distribution function g  , which satisfy the following evolution equations [45,308]: 66 Later, an incompressible multiphase LB model was proposed by Inamuro et al [46] for multiphase flows at large density ratios. Inamuro et al's model also utilized two different particle distribution functions: one for the order parameter and the other for solving the velocity field without the pressure gradient.…”
Section: Early Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 1999, He et al [45] proposed an incompressible LB model for simulating multiphase flows, in which they used an index function to track the interface between different phases. Two distribution functions were employed in the model, the index distribution function f  and the pressure distribution function g  , which satisfy the following evolution equations [45,308]: 66 Later, an incompressible multiphase LB model was proposed by Inamuro et al [46] for multiphase flows at large density ratios. Inamuro et al's model also utilized two different particle distribution functions: one for the order parameter and the other for solving the velocity field without the pressure gradient.…”
Section: Early Modelsmentioning
confidence: 99%
“…Lee and Liu [49] found that the influence of the Weber number emerges in the later stage of spreading. Lycett-Brown et al [66] have studied binary droplet collisions using a multi-speed pseudopotential LB model. Moreover, Lycett-Brown et al [354] have studied the effects of the droplet size ratio and found that the numerical errors (compared with the theoretical analysis) decrease as the droplet size ratio increases.…”
Section: Droplet Collisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through experimental investigation [1][2][3][4][5][6][7], numerical simulation [8][9][10][11][12][13][14][15][16][17], and theoretical analysis [18], much understanding has been acquired on the collision outcome, including coalescence, bouncing, and separation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to capturing the non-equilibrium effects, high-order models are also useful for other applications. For instance, by using a D2Q25 model, Daniel et at [6] have shown that high Weber number can be achievable for droplet collision simulations. Implementation of boundary conditions is crucial to application of high-order LB models.…”
Section: Introductionmentioning
confidence: 99%